Single-cell analysis reveals specific neuronal transition during mouse corticogenesis - Zhou, Ziheng; Pan, Yueyang; Zhou, Si; Wang, Shuguang; Zhang, Dengwei; Cao, Ye; Jiang, Xiaosen; Li, Jie; Zhu, Linnan; Zhao, Lijian; Gu, Shen; Lin, Ge; et al. (Frontiers in Cell and Developmental Biology, 2023)
Currently, the mechanism(s) underlying corticogenesis is still under characterization. By analyzing the developmental trajectories with single-cell RNA-sequencing datasets in mice, we identified a specific developmental sub-path contributed by a cell-population expressing both deep- and upper-layer neurons (DLNs and ULNs) specific markers, which occurred on E13.5 but was absent in adults. In this cell-population, the percentages of cells expressing DLN and ULN markers decreased and increased, respectively, during the development suggesting direct neuronal transition (namely D-T-U). Whilst genes significantly highly/uniquely expressed in D-T-U cell population were significantly enriched in PTN/MDK signaling pathways related to cell migration. Both findings were further confirmed by co-immunostaining with DLNs, ULNs and D-T-U specific markers across different timepoints. Furthermore, six genes (co-expressed with D-T-U specific markers in mice) showing a potential opposite temporal expression between human and mouse during fetal cortical development were associated with neuronal migration and cognitive functions. In adult prefrontal cortexes (PFC), D-T-U specific genes were expressed in neurons from different layers between humans and mice. In conclusion, our study characterizes a specific cell population D-T-U showing direct DLNs to ULNs neuronal transition and migration during fetal cortical development in mice. It is potentially associated with the difference of cortical development in humans and mice.